“Peran Psikiatri dalam Penatalaksanaan Depresi Postpartum Pasca Delirium pada Pasien dengan Acute Fatty Liver of Pregnancy dan Kematian Janin Intrauterin” - damba bestari; Novelita Mesah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Acute Fatty Liver of Pregnancy (AFLP) is a rare but life-threatening metabolic disorder that typically occurs in the third trimester and may lead to hepatic dysfunction, hepatic encephalopathy, and multisystem organ failure. While prompt delivery and intensive care can stabilize the patient physically, significant psychological complications may arise in the postpartum period. We report the case of a 22-year-old primigravida diagnosed with AFLP complicated by intrauterine fetal death (IUFD), hepatic encephalopathy, and delirium. The patient required 10 days of Intensive Care Unit (ICU) management before transitioning to the High Care Unit (HCU). Psychometric evaluation via the Confusion Assessment Method for the ICU (CAM-ICU) confirmed a mixed-type organic delirium, alongside a Positive and Negative Syndrome Scale–Excited Component (PANSS-EC) score of 19. After resolution of the acute organic delirium, the patient developed persistent grief, emotional lability, and severe postpartum depression, evidenced by an Edinburgh Postnatal Depression Scale (EPDS) score of 13. Her psychological distress was exacerbated by unique psychosocial stressors, particularly the concurrent healthy pregnancy of her identical twin sister, which triggered profound feelings of envy, inadequacy, and identity disruption. Management involved a tight multidisciplinary approach including Obstetrics & Gynecology, Internal Medicine, and Psychiatry. Psychiatric treatment focused on hepatic-safe pharmacotherapy using low-dose haloperidol (0.5 mg) during the acute delirium phase, followed by sertraline (25 mg) and structured Cognitive Behavioral Therapy (CBT) combined with grief counseling. At the one-month follow-up, her EPDS score improved to 10, demonstrating the crucial role of integrated medical and psychosocial care in mitigating complex bereavement and promoting neuro-psychiatric recovery following severe obstetric crises.